2007
DOI: 10.4049/jimmunol.179.6.4110
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Movements in Human Neutrophils during Phagocytosis: Characterization and Relationship to Granule Release

Abstract: Chloride ion efflux is an early event occurring after exposure of human neutrophils to several soluble agonists. Under these circumstances, a rapid and reversible fall in the high basal intracellular chloride (Cl−i) levels is observed. This event is thought to play a crucial role in the modulation of several critical neutrophil responses including activation and up-regulation of adhesion molecules, cell attachment and spreading, cytoplasmic alkalinization, and activation of the respiratory burst. At present, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 108 publications
2
24
0
Order By: Relevance
“…Transport of chloride by the plasma membrane is well-studied and chloride influx and efflux from the cytosol has been shown to be rapid and fully exchangeable [30]. Moreover, upon stimulation with neutrophil agonists, such as opsonized zymosan or formylated peptides, there is a rapid efflux of chloride from the cytosol resulting in lowering of the cytosolic chloride level from about 90-110 mM to about 50-60 mM [41]. Recent data from our laboratory show that the phagolysosomal chloride level in zymosan-activated cells is ~72 mM, similar to that in the cytosol [42].…”
Section: Discussionmentioning
confidence: 99%
“…Transport of chloride by the plasma membrane is well-studied and chloride influx and efflux from the cytosol has been shown to be rapid and fully exchangeable [30]. Moreover, upon stimulation with neutrophil agonists, such as opsonized zymosan or formylated peptides, there is a rapid efflux of chloride from the cytosol resulting in lowering of the cytosolic chloride level from about 90-110 mM to about 50-60 mM [41]. Recent data from our laboratory show that the phagolysosomal chloride level in zymosan-activated cells is ~72 mM, similar to that in the cytosol [42].…”
Section: Discussionmentioning
confidence: 99%
“…Since an inward Cl - -current represents an efflux of Cl - , K + as well as Cl - leaves the cell. Similarly, in human PMNs, phagocytosis of opsonized Candida albicans induces a Cl - -efflux [1]. Furthermore, in microglial cells and PMNs, application of Cl - -channel blockers suppresses engulfment of polystyrene MBs, E. coli , S. aureus , or C. albicans [[2,3,4], and present study].…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of opsonised Candida albicans by human polymorphonuclear neutrophil leucocytes (PMNs) triggers the efflux of Cl - in these cells [1]. Accordingly inhibition of Cl - -channel activity in human PMNs decreases the uptake of opsonized zymosan [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that Cl - plays fundamental roles in various cellular functions, such as cell cycle progression and proliferation [12, 13, 24-29], water secretion [30-32], regulation of gene expression [11, 33, 34], adhesion and migration of cells [6, 35-37], and neurite outgrowth in neuronal cells [14, 38-40]. Nakajima et al [15] have also demonstrated that microtubule polymerization was enhanced by the presence of Cl - via inhibition of intrinsic GTPase activity of α-tubulin in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, several reports have shown that Cl - channels might regulate various cellular functions such as cell cycle progression, proliferation, adhesion and migration including cancer cells [6-10]. We have previously reported that reduction of cytosolic Cl - concentration enhance gene expression of the α-subunit of epithelial Na + channel in Xenopus laevis kidney A6 cells [11].…”
Section: Introductionmentioning
confidence: 99%